A Study of Multimodal Analysis in Smartphone Advertisement - Maulydia Tamara Savitri; Rusdi Noor Rosa (Universitas Negeri Padang, 2019)
This research aims to analyze multimodal in Samsung Galaxy S9 audiovisual advertisement. The systemic functional linguistics theory by Halliday, multimodal theory by Kress and van Leeuwen and generic structure analysis theory by Cheong were applied to analyze this research. The method used in this research was a descriptive research method. The data in this research were images, texts, symbols, sounds, and gestures used in Samsung Galaxy S9 advertisement video. The source data of this research was obtained from Samsung Youtube account. The finding of this research obtained that all semiotic systems in Samsung Galaxy S9 are in harmony and complete each other. The analysis also shows that there are five generic structures found in this advertisement video; lead, display, announcement, emblem, call and visit. Meanwhile, the other structures (tag and enhancer) are not found in this advertisement.